Application of Geographic Information System to Allocate Service Areas of the Rural Road Sub-district: A Case Study of Ratchaburi Rural Road District - Tantiwutthipong, Sucheep; Meksangsouy, Pakorn; Sithi, Assamaporn (Journal of Letters, 2021)
This research studies the application of Geographic Information System (GIS) to allocate service areas of rural road sub-district offices, case study in Ratchaburi; to increase efficient road and bridge network maintenance; easier accessible to road damaged areas; and support services for commuters. This research’s data conducted by using GIS and K-means Clustering method. The results found that service areas for the rural road sub-district offices in Ratchaburi province can be clustered into 3 areas. Distribution of workloads for each office is nearly equivalent get the efficient of work better and as well as clustering patterns are reduced. Moreover, from the Nearest Neighbor Index (NNI), which is used for cluster analysis, it found that the rural road district boundary value is 0.609. Major service areas of Group 1 are mainly located in Mueang Ratchaburi District, Pak Tho District and Wat Phleng District, with NNI value 0.616. Meanwhile, major service areas of Group 2 are mainly occupied in Suan Phueng District, Ban Kha District, Chom Bueng District, which NNI value is 0.585. The last major service areas of Group 3 are covered to Photharam District, Ban Pong District, Bang Phae District, Damnoen Saduak District, which NNI value is 0.684.